IMF Quota and Governance Reform : Elements of an Agreement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper sets out, and seeks to make operational, a core package for the consideration of the Executive Board and, subsequently, the Board of Governors. The reforms would lead to a major overhaul of the Fund's quotas and governance, strengthening the Fund's legitimacy and effectiveness. The paper proposes completion of the 14th General Review of Quotas with a doubling of quotas and a major realignment of quota shares among members. It also covers proposals that would lead to a more representative, all-elected Executive Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet